1984
DOI: 10.1029/ja089ia05p02811
|View full text |Cite
|
Sign up to set email alerts
|

The wave normals of magnetospheric chorus emissions observed on board GEOS 2

Abstract: The wave normal directions of magnetospheric chorus emissions have been analyzed by using data from the geostationary GEOS 2 satellite which is located in the equatorial region at L = 6.6. As the result of analyses for a specific day of December 19, 1979, chorus is found to be generated in conjunction with substorms and at local times from around midnight to afternoon. Two types of chorus are observed: impulsive burstlike and rising tone. The chorus during midnight to late morning hours is impulsive, and at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 38 publications
13
114
1
Order By: Relevance
“…This of course depends on the plasma parameters along the reflected wave path during this particular day, but it is observed that the experimental magnetic ratio obtained in the two cases fits the theoretical one obtained by Cornilleau-Wehrlin et al (1985). Goldstein and Tsurutani (1984) and Hayakawa et al (1984) have shown that the wave normal of chorus elements at frequencies lower than one-half the electron gyrofrequency is close to the Earth's magnetic field at the equator, which seems to indicate that the generation mechanism could be due to electron cyclotron instability. It is interesting to check the values of the polar angle θ of waves returning to the equator during this event.…”
Section: Discussionsupporting
confidence: 59%
“…This of course depends on the plasma parameters along the reflected wave path during this particular day, but it is observed that the experimental magnetic ratio obtained in the two cases fits the theoretical one obtained by Cornilleau-Wehrlin et al (1985). Goldstein and Tsurutani (1984) and Hayakawa et al (1984) have shown that the wave normal of chorus elements at frequencies lower than one-half the electron gyrofrequency is close to the Earth's magnetic field at the equator, which seems to indicate that the generation mechanism could be due to electron cyclotron instability. It is interesting to check the values of the polar angle θ of waves returning to the equator during this event.…”
Section: Discussionsupporting
confidence: 59%
“…The wave vectors of ducted chorus are nearly aligned with the ambient magnetic field (Parrot et al, 2003). Chorus emissions with oblique wave normals have, however, also been observed in the vicinity of the equatorial plane (Hayakawa et al, 1984) but at frequencies above half the equatorial gyrofrequency and therefore not propagating in ducted mode.…”
Section: A B Collier and A R W Hughes: Modelling Substorm Chorusmentioning
confidence: 99%
“…• , θ is the wave-normal angle with respect to the local magnetic field direction), as found by Burton and Holzer (1974), Hayakawa et al (1984), and Agapitov et al (2011b), whereas falling tones are very oblique, as found by Cornilleau-Wehrlin et al (1976) and Santolík et al (2009).…”
Section: H Breuillard Et Al: Origin Of Falling-tone Chorusmentioning
confidence: 91%